1996
DOI: 10.1046/j.1365-313x.1996.9050639.x
|View full text |Cite
|
Sign up to set email alerts
|

Phloem‐specific expression of a plant homeobox gene during secondary phases of vascular development

Abstract: SummaryThis paper reports the isolation and characterization of a homeobox gene (VAHOXI) from Lycopersicon esculentum encoding a homeodomain protein that contains a leucine zipper motif. The bipartite homeodomain-leucine zipper (HD-Zip) motif has only been found in homeobox genes from dicotyledonous plants, indicating that this type of transcription factor regulates particular developmental processes in these plant species. Here, the genomic organization, sequence comparison and expression analysis of VAHOX1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Library Screening and DNA Sequence Analysis-A tomato genomic DNA library constructed in -EMBL3 was screened at 65°C as described (14) with the radiolabeled p26 cDNA encoding the prepro sequence of the PR-P69 protein described previously (7). The positive clones were isolated and characterized with the routine described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…Library Screening and DNA Sequence Analysis-A tomato genomic DNA library constructed in -EMBL3 was screened at 65°C as described (14) with the radiolabeled p26 cDNA encoding the prepro sequence of the PR-P69 protein described previously (7). The positive clones were isolated and characterized with the routine described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…It was found that 174 (53%) C. olitorius and 216 (63%) C. capsularis genes were expressed significantly within the fibre cells and seedlings (Supplementary Table 32). Genes encoding the WOX4, APL and HAT22 transcription factors and the TDIF signalling peptide, which are involved in vascular cambium initiation and proliferation [25][26][27][28] , were highly expressed in fibre cells, suggesting their importance in fibre differentiation. Moreover, several of the transcription factor genes involved in regulating SCW formation exhibited higher expression in the fibre cells ( Supplementary Fig.…”
mentioning
confidence: 99%
“…rearrangement of vascular bundles). Several homeobox genes were shown to preferentially express in the vascular tissues of Arabidopsis (Baima et al, 1995;Tornero et al, 1996). An Arabidopsis mutant displaying the transformation of collateral vascular bundles into amphivasal vascular bundles recently was identified (Zhong et al, 1999).…”
mentioning
confidence: 99%